2 A DIGEST OF THE LAWS OF TEXAS: CONTAINING THE LAWS IN FORCE, AND THE REPEALED LAWS ON WHICH RIGHTS REST, FROM 1754 TO 1874, at 1323 (George W. Paschal ed., 4th ed. 1874). - (:unkn) unknown (General Publisher, 1874)
Prohibited any person from carrying a pistol, other firearm, dirk, dagger, slung-shot, sword-cane, spear, brass-knuckles, bowie-knife, or any other kind of knife manufactured and sold for offense or defense into any church, religious assembly, school room, other place where persons are assembled for amusement, educational, or scientific purposes, or into a ball-room, social party, or social gathering, or any election precinct on the day of election, or places of muster or other public duty, or to any other public assembly. Violators guilty of a misdemeanor and fined not les than fifty nor more than five hundred dollars with forfeiture of the weapon on first offense. Further offenses may also be imprisoned not more than ninety days.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES